Brief Report: A Cross-Sectional Study of Anxiety Levels and Concerns of Chinese Families of Children With Special Educational Needs and Disabilities Post-first-wave of COVID-19 - Su, Xueyun; Cai, Ru Ying; Uljarević, Mirko; Van Herwegen, Jo; Dukes, Daniel; Yang, Yufang; Peng, Xiaomei; Samson, Andrea C. (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic has a multifaceted impact on mental health due to ill health, restrictions and lockdowns, and loss of employment and institutional support. COVID-19 may disproportionally impact families with special educational needs and disabilities (SEND) due to the already higher prevalence of mental health conditions in children with SEND and their parents. Therefore, it is essential to determine the short-term impact of the pandemic on the mental health of families with SEND in order to identify their ongoing health support needs. The current study aims to determine the short-term mental health impact of the pandemic on children with SEND and their parents living in China. The sample consisted of 271 parents of children with SEND aged between 6 and 17 years (Mage = 8.37; SDage = 2.76). Both child and parental anxiety levels and various concerns increased after the initial wave of COVID-19 when compared with retrospective pre-COVID-19 levels. Parental anxiety and concern levels were significantly higher for those living in rural areas compared to urban areas. In addition, parental and child anxiety and concern levels were significantly correlated with each other. Parental anxiety at the lowest level made a unique and significant statistical contribution to children’s anxiety levels. The implications of the study findings are discussed.